PROFIL LIPID PENDERITA DIABETES MELLITUS TIPE 2 P - S Josten; Mutmainnah Mutmainnah; Hardjoeno Hardjoeno (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2006)
Prevalence of type 2 diabetes mellitus (DM) tends to increasing worldwide. The main cause of death in type 2 DM is coronaryheart disease (CHD) and its mortality rate can increase 2 to 4 times compared to non-diabetics. One of the risk factors in CHD isdyslipidemia. To know the lipid profile based on age and gender and to assess the relation of total cholesterol, LDL, HDL, and TG levelto age. Descriptive retrospective study in patients with type 2 DM who are 45 years old and over. From 100 Type 2 DM patients, in theDepartment of Internal Medicine, Dr. Wahidin Sudirohusodo Hospital, Makassar, period of June to December 2005, the largest age groupwith dyslipidemia was > 59 years old, with increase LDL level, 32.73% in males and 46.67% in females. There was a significant relationbetween the in crease of TG (p = 0.03) and the decrease of HDL (p = 0.02) with age. Dyslipidemia in type 2 DM patients at age group> 59 years old was shown by an increase in LDL level. The increase of TG and decrease of HDL level were significant in all age groups.Restriction of this study was not to check the antilipidemic medicine used. Early dyslipidemia of Type 2 DM should be known by lipidfraction determination and further dyslipidemia study should be conducted to predict the risk of CHD.